Holy rebellion: religious feminism and the transformation of Judaism and women's rights in Israel - ʻIr-Shai, Ronit (Brandeis series on gender, culture, religion, and law, 2024)
"Holy Rebellion" examines the shifting entanglements of religion, gender, and law in times of cultural transformation. Irshai and Zion-Waldoks explore theological, halakhic, political, and sociological processes to show how they advance women's rights and are met with a conservative backlash. The authors analyze the reciprocity of cultural narratives and legal norms, and propose "narrative ripeness" and "dignity" tests to assess how change within a minority cultural community may be accelerated or hindered by state intervention